Popular science book on the Ficus genus at Lambung Mangkurat University Campus: Its effectiveness in training students' critical thinking - Muhammad Farhan Azhari; Mochamad Arief Soendjoto; Aminuddin Prahatama Putra; Maulana Khalid Riefani (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
There is no popular science book (PSB) on the genus Ficus, especially those that grow and develop specifically in the Lambung Mangkurat University Campus Area, Banjarmasin and Banjarbaru. Equipped with questions and invitations related to critical thinking, the PSB was compiled and then tested. The aim was to measure the effectiveness of the PSB to train students' critical thinking. The valid PSB was tested with a small group test involving 20 students and a field test involving 25 students. In three meetings, the first meeting was only as an exercise and was not assessed and meetings 2 and 3 were assessed by observers, students were asked to carry out practicums based on student worksheets and answer 10 questions. The values were analyzed so that from the small group test the expected effectiveness was obtained and from the field test the actual effectiveness was obtained. An increase in quantitative values occurred from meeting 2 to next meeting, both for expected effectiveness (from 69.10 to 84.60) and actual effectiveness (from 67.80 to 86.10). With an increase from quite good to very good in the two effectiveness, the PSB on the Ficus genus is effective in training students' critical thinking.Abstrak. Belum ada buku ilmu pengetahuan populer (BIP) tentang genus Ficus, apalagi yang tumbuh dan berkembang khusus di Area Kampus Universitas Lambung Mangkurat, Banjarmasin dan Banjarbaru. Dilengkapi dengan pertanyaan dan ajakan terkait dengan berpikir kritis, BIP tersebut disusun dan kemudian diuji. Tujuannya adalah untuk mengukur efektivitas BIP itu untuk melatihkan berpikir kritis mahasiswa. BIP yang sudah valid diuji dengan uji kelompok kecil yang melibatkan 20 mahasiswa dan uji lapangan yang melibatkan 25 mahasiswa. Dalam tiga pertemuan yang pertemuan pertamanya hanya sebagai latihan dan tidak dinilai serta Pertemuan-2 dan Pertemuan-3 dinilai oleh observer, mahasiswa diminta melaksanakan praktikum berdasarkan lembar kerja mahasiswa dan menjawab 10 pertanyaan. Nilai-nilainya dianalisis sehingga dari uji kelompok kecil diperoleh efektivitas harapan dan dari uji lapangan diperoleh efektivitas aktual. Peningkatan nilai kuantitatif terjadi dari Pertemuan-2 ke Pertemuan-3, baik untuk efektivitas harapan (dari 69,10 ke 84,60) maupun efektivitas aktual (dari 67,80 ke 86,10). Dengan peningkatan dari cukup baik ke sangat baik pada dua efektivitas tersebut, BIP tentang genus Ficus tersebut efektif untuk melatihkan berpikir kritis mahasiswa.